Diagnostic and Prognostic Biomarkers in the Rational Assessment of Mesothelioma (DIAPHRAGM) study: protocol of a prospective, multicentre, observational study. Issue 11 (24th November 2016) - Tsim, Selina; Kelly, Caroline; Alexander, Laura; McCormick, Carol; Thomson, Fiona; Woodward, Rosie; Foster, John E; Stobo, David B; Paul, Jim; Maskell, Nick A; Chalmers, Anthony; Blyth, Kevin G
Abstract : Introduction: Malignant pleural mesothelioma (MPM) is an asbestos-related cancer, which is difficult to diagnose. Thoracoscopy is frequently required but is not widely available. An accurate, non-invasive diagnostic biomarker would allow early specialist referral, limit diagnostic delays and maximise clinical trial access. Current markers offer insufficient sensitivity and are not routinely used. The SOMAmer proteomic classifier and fibulin-3 have recently demonstrated sensitivity and specificity exceeding 90% in retrospective studies. DIAPHRAGM (Diagnostic and Prognostic Biomarkers in the Rational Assessment of Mesothelioma) is a suitably powered, multicentre, prospective observational study designed to determine whether these markers provide clinically useful diagnostic and prognostic information. Methods and analysis: Serum and plasma (for SOMAscan and fibulin-3, respectively) will be collected at presentation, prior to pleural biopsy/pleurodesis, from 83 to 120 patients with MPM, at least 480 patients with non-MPM pleural disease and 109 asbestos-exposed controls. Final numbers of MPM/non-MPM cases will depend on the incidence of MPM in the study population (estimated at 13–20%). Identical sampling and storage protocols will be used in 22 recruiting centres and histological confirmation sought in all cases. Markers will be measured using the SOMAscan proteomic assay (SomaLogic) and a commercially available fibulin-3 ELISA (USCN Life Science). The SE in the estimated sensitivity and specificity will be <5% for each marker and their performance will be compared with serum mesothelin. Blood levels will be compared with paired pleural fluid levels and MPM tumour volume (using MRI) in a nested substudy. The prognostic value of each marker will be assessed and a large bioresource created. Ethics and dissemination: The study has been approved by the West of Scotland Research Ethics Committee (Ref: 13/WS/0240). A Trial Management Group meets on a monthly basis. Results will be published in peer-reviewed journals, presented at international meetings and disseminated to patient groups. Trial registration number: ISRCTN10079972, Pre-results.